The Application of The Game Methods and Interest to Elementary School Studentsâ€™ Learning Outcomes of Fundamental Movement Skills in Running - Rahma Dewi; Bessy Sitorus Pane; Nurkadri Nurkadri; Amirsyah Putra Lubis (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This research aimed to determine the application of the game methods and interest to Elementary School studentsâ€™ learning outcomes of fundamental movement skills in running. The research samples consisted of 60 third-grade elementary school students. This research used treatment by level 2x2 research design with Tukey's test at the level of 16Ã¢Ë†Â"> Â = 0.05. The results showed: 1) Qh=12.40 and Qt=3.83 in groups A1 and A2. Based on these results, it can be concluded that there were differences in learning outcomes of fundamental movement skills in running between-group game methods and individual game methods. 2) The Fh > Ft was 19.81 > 4.15. In conclusion, there was an interaction between the game methods and learning interest on fundamental movement skills in running. 3) The result of the Tukeyâ€™s test in groups A1B1 and A2B1 included Qh = 11.27 and Qt = 2.99. Based on these results, it can be concluded that the learning outcomes of fundamental movement skills in running with high interest taught using the group game method were better than the individual game method. 4) Furthermore, the Qh=1.32 and Qt=2.99. Based on these results, it could be concluded that the learning outcomes of low-interest fundamental movement skills in running taught using the group game method were not better than the individual game method.